2003
DOI: 10.1007/s00592-003-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing genetic factors for diabetic polyneuropathy in patients with type 1 diabetes: a population-based case-control study

Abstract: Oxidative stress plays a key role in the development of microvascular complications of diabetes mellitus (DM). Antioxidant enzymes protect against the rapid onset of diabetic polyneuropathy (DPN) by reducing oxidative stress. Genetic variations that affect activity or expression levels of the antioxidant enzymes may therefore be associated with susceptibility to DPN. We examined polymorphic markers Ala(-9)Val in SOD2 gene and Arg213Gly in SOD3 gene for possible relation to DPN in Russian type 1 diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
1
16
0
8
Order By: Relevance
“…In agreement with our results, Strokov et al showed that Ala(-9)-Val polymorphism in a Russian population was associated with a high risk of the development of neuropathy in type 1 diabetic patients [8]. Nosikov and colleagues concluded that diabetic polyneuropathy is associated with single-nucleotide polymorphism, such as Ala(-9)-Val of the SOD 2 gene, Arg 213-Gly of SOD 3, and T(-262)-C of CAT, and with a polymorphic microsatellite of the nitric oxide synthase gene [9].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our results, Strokov et al showed that Ala(-9)-Val polymorphism in a Russian population was associated with a high risk of the development of neuropathy in type 1 diabetic patients [8]. Nosikov and colleagues concluded that diabetic polyneuropathy is associated with single-nucleotide polymorphism, such as Ala(-9)-Val of the SOD 2 gene, Arg 213-Gly of SOD 3, and T(-262)-C of CAT, and with a polymorphic microsatellite of the nitric oxide synthase gene [9].…”
Section: Discussionsupporting
confidence: 94%
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
“…Na + /K + -ATPase may be influenced by metabolic control and C-peptide secretion [101]. Some single nucleotide polymorphisms (SNPs) have been studied in Russian T1D patients with DSPN: these relate to the poly(ADPribose)polymerase-1 gene, the catalase gene, and genes encoding the enzymes superoxide dismutase extracellular superoxide dismutase [102][103][104]. In Greek T2D patients, the D allele of the Alpha2B adrenoceptor has been found to be associated with presence and severity of DSPN [105].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…В опреде-ленной мере эту теорию подтверждают факты о связи сроков развития ДПН у больных СД с полиморфизмом определенных генов. Найдена ассоциация сроков разви-тия ДПН с полиморфизмом генов митохондриальной и эндотелиальной супероксиддисмутазы и гена PARP, что хорошо согласуется с представлением о ведущей роли ми-тохондриального супероксида в формировании поздних осложнений СД [12,13].…”
unclassified